1996
DOI: 10.1111/j.1532-5415.1996.tb02435.x
|View full text |Cite
|
Sign up to set email alerts
|

A Walking Program for Nursing Home Residents: Effects on Walk Endurance, Physical Activity, Mobility, and Quality of Life

Abstract: Twelve weeks of daily walking at a self-selected walking pace by ambulatory nursing home residents produced significant improvements in walk endurance capacity. No other significant changes were noted in physical activity level, mobility, or quality of life in either group after the intervention. Also, there were no side effects, such as increases in falls or cardiovascular complications, due to the walking intervention. Lengthening the walking program to 22 weeks produced no further significant changes in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(87 citation statements)
references
References 9 publications
0
81
0
5
Order By: Relevance
“…In residents of a nursing home who were assigned to a 12-week walking program, the experimental walking group improved distance by 22% after the program, whereas no significant changes were reported for the social visit control group. 28 The effects of walking have also been proved to be successful in a study of patients assigned to an experimental (diet and exercise) group, who were instructed to walk at least 10 000 steps/day on a flat field vs a diet alone control group, who maintained a normal routine (45007290 steps/day). The experimental group showed a significantly greater amount of weight reduction (7.870.8 vs 4.270.5 kg, Po0.01) and had significant correlations between metabolic clearance rate and average steps walked per day (r ¼ 0.7257, Po0.005).…”
Section: Discussionmentioning
confidence: 99%
“…In residents of a nursing home who were assigned to a 12-week walking program, the experimental walking group improved distance by 22% after the program, whereas no significant changes were reported for the social visit control group. 28 The effects of walking have also been proved to be successful in a study of patients assigned to an experimental (diet and exercise) group, who were instructed to walk at least 10 000 steps/day on a flat field vs a diet alone control group, who maintained a normal routine (45007290 steps/day). The experimental group showed a significantly greater amount of weight reduction (7.870.8 vs 4.270.5 kg, Po0.01) and had significant correlations between metabolic clearance rate and average steps walked per day (r ¼ 0.7257, Po0.005).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for why this improvement was not observed in patients with more severe cognitive impairment might be that the group with mild cognitive problems benefited from the social aspects of the exercise intervention which in turn impacted on their mood. Another Class II study (Schnelle,dementia 5( 3 ) MacRae, Ouslander, Simmons, & Nitta, 1995) found a decrease of agitation in both groups, implying no additional benefit of the exercises on agitation, and MacRae et al (1996) found no significant change in outcome. However, both studies offered an exercise intervention of relatively short duration, in other words, 13 minutes and 14.5 to 23.8 minutes respectively.…”
Section: Effects Of Physical Activity On Affective Behaviourmentioning
confidence: 99%
“…It has a bene®cial impact on functional, physical and psychological health. A higher level of physical activity has been associated with increased survival (Morgan & Clarke, 1997), a delay in the progression of disability (Fries, 1996) and loss of functional ability (Ho et al, 1997), improved balance and strength (Wolfson et al, 1996;Wolf et al, 1996), reduced incidence of falls (and hence risk of fractures; Campbell et al, 1997), as well as higher quality of life (MacRae et al, 1996;Ruuskanen & Ruoppila, 1995).…”
Section: Physical Activitymentioning
confidence: 99%